Fatty Acid Synthase Correlates With Prognosis-Related Abdominal Adipose Distribution and Metabolic Disorders of Clear Cell Renal Cell Carcinoma - Xu, Wenhao; Hu, Xiaoxin; Anwaier, Aihetaimujiang; Wang, Jun; Liu, Wangrui; Tian, Xi; Zhu, Wenkai; Ma, Chunguang; Wan, Fangning; Shi, Guohai; Qu, Yuan-Yuan; Zhang, Hailiang; et al. (Frontiers in Molecular Biosciences, 2021)
Purpose: Lipid metabolism reprogramming is a major pathway in tumor evolution. This study investigated fatty acid synthase (FASN) mRNA expression in anthropometric adipose tissue and elucidated the prognostic value and potential mechanism of clear cell renal cell carcinoma (ccRCC). Materials and Methods: Transcription profiles were obtained from 533 ccRCC samples in TCGA cohorts. RT-qPCR and immunohistochemistry were performed to detect FASN expression in 380 paired ccRCC and normal tissues from the Fudan University Shanghai Cancer Center (FUSCC). Visceral adipose tissue (VAT) and subcutaneous adipose tissue were at the level of the umbilicus as measured by MRI. Non-targeted metabolomics and in vitro experiments were used to reveal the biological functions of FASN. Results: Increased FASN expression was significantly relevant to advanced T, N, and AJCC stages (p<0.01) and significantly correlated to poor PFS and OS of 913 ccRCC patients in FUSCC and TCGA cohorts. Pearson’s correlation coefficient indicated that FASN amplification was positively correlated to VAT% (r=0.772, p<0.001), which significantly correlated to poor PFS (HR=2.066, p=0.028) and OS (HR=2.773, p=0.023) in the FUSCC cohort. Transient inhibition or overexpression of FASN significantly regulated A498 and 786O cell proliferation and migration by regulating epithelial-mesenchymal transition. Inhibition of FASN led to a higher apoptotic rate and decreased lipid droplet formation compared with normal control in ccRCC cells. Non-targeted metabolomics showed that decreased de novo lipogenesis might be required to sustain an elevation of glycolytic activity in 786O cells by regulating galactinol, DL-lactate, N-acetylaspartylglutamate, and sucrose, thereby participating in carcinogenesis and progression of ccRCC Conclusion: This study demonstrated that FASN expression is positively related to aggressive cell proliferation, migration, apoptosis, and lipid droplet formation and regulates metabolic disorders of the ccRCC microenvironment. Additionally, elevated FASN mRNA expression is significantly correlated to the abdominal obesity distribution, especially VAT%, which is a significant predictor of a poor prognosis for ccRCC patients.